2019
DOI: 10.7717/peerj.7745
|View full text |Cite
|
Sign up to set email alerts
|

Validation of COI metabarcoding primers for terrestrial arthropods

Abstract: Metabarcoding can rapidly determine the species composition of bulk samples and thus aids biodiversity and ecosystem assessment. However, it is essential to use primer sets that minimize amplification bias among taxa to maximize species recovery. Despite this fact, the performance of primer sets employed for metabarcoding terrestrial arthropods has not been sufficiently evaluated. This study tests the performance of 36 primer sets on a mock community containing 374 insect species. Amplification success was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(167 citation statements)
references
References 91 publications
3
163
0
1
Order By: Relevance
“…By designing specific primers, amplification biases were minimized and the recovery of BALOs taxa maximized (Elbrecht et al, 2019). Globally, some of our primers worked properly for the different tested ecosystems and we are confident they could be applied successfully to other systems, even if further testing and optimization may be required.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…By designing specific primers, amplification biases were minimized and the recovery of BALOs taxa maximized (Elbrecht et al, 2019). Globally, some of our primers worked properly for the different tested ecosystems and we are confident they could be applied successfully to other systems, even if further testing and optimization may be required.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, Bacteriovorax primer p584F -p874R might also be concerned with most likely Peredibacter being more present than Bacteriovorax as reported by Paix et al (2019). Finally, primers' performance could be related to other reasons that we did not explore here such as DNA polymerase (Śpibida et al, 2017), the number of PCR cycles or the cell GC content (Elbrecht et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Some of the early microbiome literature used only a single primer set to produce single amplicon datasets, and this has facilitated large scale studies and brought a measure of standardization to the field (Gilbert et al, 2014;Thompson et al, 2017). There are many examples, however, showing the effect of primer bias for a variety of commonly used metabarcoding primers (Hong et al, 2009;Bellemain et al, 2010;Clarke et al, 2014;Gibson et al, 2014;Elbrecht et al, 2019;Hajibabaei et al, 2019). There is also difficulty in designing "universal" COI primers to capture broad swaths of phylogenetic diversity and a switch to a multi-marker approach has been proposed for assessing animal diversity (Deagle et al, 2014).…”
Section: How Does Cluster Methods Choice Affect Diversity Analyses?mentioning
confidence: 99%
“…Nevertheless, multiple studies have shown that there is room for considerable improvements to better bridge the current gaps between taxonomy-dependent molecular and morphology-based approaches. Taxonomic breadth in HTS data could be broadened by carefully designing novel amplification primers (Elbrecht et al, 2019) or using more than one primer pair (Corse et al, 2019). Applying correction factors to read counts, based on established knowledge of the biovolume (Vasselon et al, 2018), the number of copies of the targeted marker (Vetrovský, et al, 2013) or by spiking samples with known internal standard for quantitative determinations (Tkacz et al, 2018;Ji et al, 2019), are all promising methods for resolving these challenges.…”
Section: The Environmental Genomics Revolution For Biodiversity Reseamentioning
confidence: 99%